FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS HIDUP PEREMPUAN KLIMAKTERIK - Yanita Trisetiyaningsih (Universitas Jenderal Achmad Yani Yogyakarta, 2016)
Background:Physical and psychological changes during climacterium phase could influence quality of life in climacteric women. Eightypercent of womenreported anydiscomfortthat occurs as climactericsymptomssuch asheadaches, sexual problems, tachycardia, hot flushes, sweatingandinsomniathat can significantlydegrade the quality oflive. Factorsthat determinethe quality of lifeare age, menopauseduration, marital status, education level, income, employment status, healthstatus, health insurance, and parity. Objective: The purpose of the study was to determine thefactorsassociated withthe quality of life ofclimactericwomen. Methods: The study wasa quantitave research with cross sectional design. The samples were 88 subjects. Data collection used Menopause Rating Scale (MRS) and the WHOQOL-BREF.The data analysis used Spearman rank correlation test and contingency coefficient. Result: There was a significant relationship between parity and employment status with quality of life (p<0.05), but not to the variables of age, duration of menopause, marital status, education level, income, and health insurance. Conclusion: There was a significant relationship between parity and employment status with quality of lifein climacteric women. Keyword: Quality of life, climacteric women